2019
DOI: 10.1016/j.ebiom.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 coordinates adiponectin to mediate the beneficial effects of low-protein diet on primordial follicle reserve

Abstract: Background Global consumption of protein per capita is rising, while rates of infertility are increasing. However, a clear relationship between protein intake and reproductive health has not been demonstrated. The activation of the quiescent primordial follicles is the first step of folliculogenesis, and their activation must be tightly controlled to prevent premature exhaustion of the ovarian follicular reserve. Methods The primordial follicle reserve of wild-type or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 74 publications
1
51
0
Order By: Relevance
“…The FGF21 liverspecific knockout (FGF21LKO) mice have been previously characterized. 29,35 Briefly, FGF21 loxp/loxp mice from Jackson Laboratory (022361; Bar Harbor, ME, USA) were mated with Alb-Cre mice from Nanjing University (J003574; Model Animal Research Center, Nanjing, China) to generate FGF21 loxp+/-, Alb-Cre mice. And then FGF21 loxp+/-, Alb-Cre mice were mated with FGF21 loxp/loxp mice to generate FGF21 loxp/loxp, Alb-Cre .…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FGF21 liverspecific knockout (FGF21LKO) mice have been previously characterized. 29,35 Briefly, FGF21 loxp/loxp mice from Jackson Laboratory (022361; Bar Harbor, ME, USA) were mated with Alb-Cre mice from Nanjing University (J003574; Model Animal Research Center, Nanjing, China) to generate FGF21 loxp+/-, Alb-Cre mice. And then FGF21 loxp+/-, Alb-Cre mice were mated with FGF21 loxp/loxp mice to generate FGF21 loxp/loxp, Alb-Cre .…”
Section: Animalsmentioning
confidence: 99%
“…RNA extraction and RT-PCR were performed as previously reported. 29,35 Briefly, RNA from ovarian was extracted by Trizol (15596018; Thermo Fisher Scientific) and purified using RNA mini-columns (RR037A; Takara Bio). RT-PCR was conducted in 10 μl of reaction volume with SYBR Green (RR820A; Takara Bio).…”
Section: Rna Extraction and Gene Expression Analysismentioning
confidence: 99%
“…In line with this, a previous study reported that the concentration of FGF21 was chronically elevated from late pregnancy to lactation in high-yielding dairy cows, which was accompanied with intense lipid mobilization [24]. Moreover, FGF-21 may function as an endocrine factor to regulate body composition changes during lactation by inducing gluconeogenesis and fatty acid oxidation [25,26]. In rodents, FGF21 overexpression is shown to cause infertility, such as delayed vaginal opening, reduced mating, and anovulatory hypogonadism [27].…”
Section: Reproductive Performance and Plasma Hormonesmentioning
confidence: 69%
“…At the end of amplification, dissociation analyses of the PCR product were performed to confirm the specificity of PCR products. The relative mRNA abundance of analyzed genes was calculated using the method of 2 −∆∆Ct , as described previously [23]. In addition, the percentages of myosin heavy chain (MyHC) isoforms were calculated as the ratio of the normalized expression level of each MyHC isoform to the total expression of MyHC [24].…”
Section: Real-time Reverse Transcription-pcr (Rt-pcr) Analysismentioning
confidence: 99%